Lectin complement pathway proteins in healthy individuals - Troldborg, A. (Clin Exp Immunol, 2017)
Since the discovery of the lectin pathway of complement activation, numerous clinical cohorts have been examined for one or more proteins, with the intention of uncovering the functions of the proteins or with the aim of discovering new biomarkers or diagnostic tools. To unveil the abnormal, it is pivotal to know the normal. Our aim was to describe the concentrations of the 11 known proteins of the lectin pathway in serum and plasma and to uncover possible gender differences, age and diurnal variations, which must be taken into account for investigation in different cohorts. We examined the concentrations of all lectin pathway proteins mannan‐binding lectin (MBL), H‐ficolin, L‐ficolin, M‐ficolin, collectin‐K1, collectin‐L1, MBL‐associated serine protease 2 (MASP‐2), MASP‐3, MBL‐associated protein of 44 kDa (MAp44) and MAp19 in 300 Danish blood donors in serum and ethylenediamine tetraacetic acid (EDTA) plasma in established assays, and we further developed a new assay to measure MASP‐1 in the same samples. We found significant differences in concentrations between serum and plasma for all proteins except for MBL and MASP‐3. H‐ficolin, M‐ficolin and MAp19 displayed convincing diurnal variation. H‐ficolin, in particular, halved from morning to the middle of the night. There were gender differences for most proteins, whereas age did not seem to influence concentration. The present study underlines the necessity of considering which material to use, correct matching and a trial design that takes the nature of the protein into account in order for the outcome of cohort studies to have significant relevance.